2013
DOI: 10.1186/1746-6148-9-213
|View full text |Cite
|
Sign up to set email alerts
|

Method to grow Actinobacillus pleuropneumoniaebiofilm on a biotic surface

Abstract: BackgroundActinobacillus pleuropneumoniae is a Gram-negative bacterium and a member of the Pasteurellaceae family. This bacterium is the causative agent of porcine pleuropneumonia, which is a highly contagious respiratory disease causing important economical losses to the worldwide pig industry. It has been shown that A. pleuropneumoniae can form biofilms on abiotic surfaces (plastic and glass). Although in vitro models are extremely useful to gain information on biofilm formation, these models may not be repr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 22 publications
0
19
0
3
Order By: Relevance
“…Several virulence factors of A. pleuropneumoniae have been identified and these include the Apx toxins, iron uptake systems, adhesins and surface polysaccharides (Bossé et al ., ; Chiers et al ., ). We have shown that A. pleuropneumoniae is able to produce a dense biofilm on abiotic (plastic and glass; Labrie et al ., ; Tremblay et al ., ) and biotic (cell line; Tremblay et al ., ) surfaces. We have also shown that A. pleuropneumoniae biofilm cells were 100–30 000 times more tolerant to ampicillin, florfenicol, tiamulin or tilmicosin than their planktonic counterparts (Archambault et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Several virulence factors of A. pleuropneumoniae have been identified and these include the Apx toxins, iron uptake systems, adhesins and surface polysaccharides (Bossé et al ., ; Chiers et al ., ). We have shown that A. pleuropneumoniae is able to produce a dense biofilm on abiotic (plastic and glass; Labrie et al ., ; Tremblay et al ., ) and biotic (cell line; Tremblay et al ., ) surfaces. We have also shown that A. pleuropneumoniae biofilm cells were 100–30 000 times more tolerant to ampicillin, florfenicol, tiamulin or tilmicosin than their planktonic counterparts (Archambault et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Actinobacillus pleuropneumoniae non-hemolytic and non-cytotoxic MBHPP147 was kindly provided by Ruud P.A.M. Segers (MSD Animal Health, Boxmeer, The Netherlands). This strain is a mutant of the serotype 1 reference strain S4074 producing non-active ApxI and ApxII toxins (AppΔapxICΔapxIIC) [41]. Bacteria was grown at 37°C in brain heart infusion broth (BHI; Oxoid Ltd., Basingstoke, Hampshire, England) or in BHI agar The PRRSV North American reference strain IAF-Klop was used in this study.…”
Section: Bacterial and Viral Strainsmentioning
confidence: 99%
“…O contágio geralmente ocorre após inalação de aerossóis ou contato direto, o microrganismo inalado coloniza o tecido pulmonar aderindo-se ao muco, proteínas e a células hospedeiras com posterior multiplicação no local (Chiers et al 2010). O monitoramento do status da doença em rebanhos, o controle e a erradicação são de fundamental importância devido a características de contágio rápido deste agente, para impedir que animais portadores sejam introduzidos em rebanhos saudáveis (Tremblay et al 2013).…”
Section: Introductionunclassified
“…O contágio geralmente ocorre após inalação de aerossóis ou contato direto, o microrganismo inalado coloniza o tecido pulmonar aderindo-se ao muco, proteínas e a células hospedeiras com posterior multiplicação no local (Chiers et al 2010). O monitoramento do status da doença em rebanhos, o controle e a erradicação são de fundamental importância devido a características de contágio rápido deste agente, para impedir que animais portadores sejam introduzidos em rebanhos saudáveis (Tremblay et al 2013).Testes indiretos são muito utilizados (Machado et al 2001, Shin et al 2011, Eamens et al 2012a,b, GimenezLirola et al 2014,para detecção simultânea de anticorpos para toxinas com sensibilidade de 82,7% e especificidade de 100% (Gimenez-Lirola et al 2014). São descritos testes de ELISA monovalentes e polivalentes para sorotipos, com sensibilidade e especificidade variando de 88,3% a 96,6% (Machado et al 2001).…”
unclassified